(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This research seeks to identify the reality of storytelling teaching and its role in the acquisition and development of linguistic competence for primary school children in Morocco, as well as describe and analyse the structural and didactic difficulties faced by school teachers when using storytelling. To attain the aims of our research, a questionnaire was administered with a sample of 100 teachers from public and private schools, covering both urban and rural settings. The analysis of the findings uncovers a lack of knowledge of storytelling structure and an almost total absence of teacher training in storytelling didactics. In light of the findings, it appears that the role of storytelling in teaching is significant for the acquisition and development of linguistic competence; hence, teachers must be well qualified in this area, both in the pre-service and in-service (continuing) training. Finally, we have outlined the study’s strengths and limitations and proposed several recommendations to improve the current situation.